2007
DOI: 10.1542/peds.2006-2023j
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid-Induced Osteoporosis in Children: Impact of the Underlying Disease

Abstract: Glucocorticoids inhibit osteoblasts through multiple mechanisms, which results in significant reductions in bone formation. The growing skeleton may be especially vulnerable to adverse glucocorticoid effects on bone formation, which could possibly compromise trabecular and cortical bone accretion. Although decreased bone mineral density has been described in various pediatric disorders that require glucocorticoids, and a population-based study reported increased fracture risk in children who require Ͼ4 courses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(69 citation statements)
references
References 83 publications
(92 reference statements)
0
65
0
4
Order By: Relevance
“…Gulati et al (32) demonstrated a decreased BMC of the spine in a group of 100 children with NS in 61% of these patients. In contrast, Leonard and colleagues (33,34) could not show significant deficits in BMC in 60 children aged 9.0 Ϯ 3.4 yr with glucocorticoid-sensitive NS, when correction was made for bone area, age, gender, race, and Tanner stage. Only one study dealt with adults who were treated for childhood NS: Hegarty et al (35) found in 34 adults a significantly decreased distal radial trabecular volumetric BMD (mean T score Ϫ1.04).…”
Section: Bone Mineral Densitymentioning
confidence: 75%
“…Gulati et al (32) demonstrated a decreased BMC of the spine in a group of 100 children with NS in 61% of these patients. In contrast, Leonard and colleagues (33,34) could not show significant deficits in BMC in 60 children aged 9.0 Ϯ 3.4 yr with glucocorticoid-sensitive NS, when correction was made for bone area, age, gender, race, and Tanner stage. Only one study dealt with adults who were treated for childhood NS: Hegarty et al (35) found in 34 adults a significantly decreased distal radial trabecular volumetric BMD (mean T score Ϫ1.04).…”
Section: Bone Mineral Densitymentioning
confidence: 75%
“…(26) In vitro studies have shown that serum from newly diagnosed pediatric subjects with Crohn's disease was associated with lower in vitro rat osteoblast activity when compared with serum from healthy controls. (27) Furthermore, rat bone cultures exposed in vitro to sera of patients with Crohn's disease manifested evidence of decreased mineralization and disorganized osteoid deposition.…”
Section: Discussionmentioning
confidence: 99%
“…If a clinician elects to initiate a trial of immunosuppressive therapy, the patient should be closely monitored for side effects. This may include bone density scanning, serial growth measurements, and ophthalmologic screening in children receiving chronic corticosteroids (199,200), or periodic complete blood counts and ophthalmologic evaluations in children receiving chronic hydroxychloroquine (201,202).…”
Section: Pharmacological Therapymentioning
confidence: 99%